2021
DOI: 10.1029/2021ja029388
|View full text |Cite
|
Sign up to set email alerts
|

Re‐Reconnection Processes of Magnetopause Flux Ropes: Three‐Dimensional Global Hybrid Simulations

Abstract: Flux ropes (FRs) are magnetic structures composed of helical magnetic field lines, which are universal in space. The FRs act as flux transfer events (FTEs) at the Earth's magnetopause (e.g., Russell & Elphic, 1978), plasmoids in the magnetotail (Zong et al., 2004), and coronal mass ejection in the heliosphere (Ruffenach et al., 2012). Earth's magnetopause FRs play an important role in the transfer of energy and plasma from the solar wind into the magnetosphere during the southward interplanetary magnetic field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…These FTEs may coalesce with each other because of their different propagating speeds, and new FTEs are generated at the magnetopause near Mercury. The coalescence of FTEs is a re-reconnection process, which has also been well simulated and studied by performing 3D global hybrid simulations at the Earth's magnetopause (Guo et al 2021a(Guo et al , 2021b(Guo et al , 2021c and ubiquitously observed in planetary magnetospheres (Wang et al 2017;Zhou et al 2017;Zhong et al 2020). At t = 135.72 s, F2 and F3 have merged into one FTE "F2,3," and a new FTE "F4" appears at about x = −0.5R M .…”
Section: Simulation Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…These FTEs may coalesce with each other because of their different propagating speeds, and new FTEs are generated at the magnetopause near Mercury. The coalescence of FTEs is a re-reconnection process, which has also been well simulated and studied by performing 3D global hybrid simulations at the Earth's magnetopause (Guo et al 2021a(Guo et al , 2021b(Guo et al , 2021c and ubiquitously observed in planetary magnetospheres (Wang et al 2017;Zhou et al 2017;Zhong et al 2020). At t = 135.72 s, F2 and F3 have merged into one FTE "F2,3," and a new FTE "F4" appears at about x = −0.5R M .…”
Section: Simulation Resultsmentioning
confidence: 96%
“…Flux transfer events (FTEs), a series of distinct bipolar perturbations in the magnetic field component normal to the planetary magnetopause, topologically connect the interplanetary and planetary magnetic fields in the magnetopause (Russell & Elphic 1978), and provide a channel for mass and energy from the solar wind to the planetary magnetosphere (Lockwood & Moen 1999;Paschmann et al 1982;Hasegawa et al 2006;Kuznetsova et al 2009;Tan et al 2011;Dong et al 2017;Sun et al 2022). It is generally believed that FTEs are essentially magnetic flux ropes formed in multiple X-line reconnection occurring in the magnetopause current sheet (Lee & Fu 1985;Zhong et al 2013;Fuselier et al 2018;Guo et al 2020). FTEs were first reported at the magnetopause of Earth with the ISEE satellite (Russell & Elphic 1978), and now are commonly observed in other magnetized planetary magnetopauses (Russell & Walker 1985; Jasinski et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…R. Sun et al, 2019). In addition, the dynamics of FTEs have been previously captured in three-dimensional (3D) hybrid-particle in cell (PIC) simulations (Guo et al, 2021a(Guo et al, , 2021bTan et al, 2011). In this study, we add to previous research by using the global hybrid-Vlasov code Vlasiator (Palmroth et al, 2018) to construct a high-resolution spatiotemporal assessment of the energy flux through the magnetopause during FTEs.…”
mentioning
confidence: 99%
“…Moreover, J. Guo et al. (2021a, 2021b) used a 3‐D global hybrid simulation to show that when the IMF is southward, the number of flux ropes is 4–8, the length of flux ropes can be up to 12 RE and the diameter of the flux ropes can be up to 2 RE. However, in this study, we find that when the IMF is northward, the number of flux ropes is 1–2, the length of flux ropes is only about 3 RE and the diameter of the flux ropes is less than 1 RE.…”
Section: Conclusion and Discussionmentioning
confidence: 99%